PROFUT: an analysis of the capital structure of Brazilian soccer teams - Erika Maia da Rocha; Francisco Ícaro Silvério de Oliveira; Rosângela Queiroz Souza Valdevino (Revista Ambiente Contábil, 2021)
Purpose: The research intends to verify the relationship between meeting the requirements for joining and staying at PROFUT and the economic and financial situation of Brazilian football clubs listed in the Ranking Nacional de Clubes (RNC).